Public budget for health in Peru for the 2019-2024 period - Zuñiga Olivares, Miguel Armando (2024)
Introduction. In Peru, public budget laws define the level and initial distribution of the health budget. Objective. To analyze the evolution of the level and initial distribution of the health budget in Peru in the period 2019-2024. Methods. Descriptive study. The budget of the Health function was analyzed by budget categories, budget programs, levels of government and departments, from 2019 to 2024, according to data from the Ministry of Economy and Finance. Results. Between 2019 and 2024, the budget for the Health function increased by 35%; while its share in the budget of the General Government increased from 10.8% to 12.2%, respectively. Also, the participation of budgetary programs in the budget decreased; while participation of Regional Governments increased. Between 2019 and 2024, budget programs related to mental health, cancer and emergency and emergency medical care saw a progressive and significant increase in their budget; in contrast, budget programs related to non-communicable diseases, metaxians and zoonoses and tuberculosis-HIV/AIDS had a lower budget than in 2019. Also, 50% of the budget of the Health function was concentrated in 2 or 3 departments, mainly in Lima. Conclusions. There was a general increase in the health budget, although its evolution was irregular. This increase favored actions not linked to results, as well as regional governments. Some budget programs actually lost resources. Few departments concentrated much of the budget.